Критическая социология Франкфуртской школы: между наукой и идеологией - Литовченко, Артём Дмитриевич; Литовченко, Артем Дмитрович; Lytovchenko, Artem D. (Східноєвропейський національний університет імені Лесі Українки, 2014)
Критическая социология Франкфуртской школы остаётся практически вне поля зрения отечественного академического социологического сообщества, хотя именно она подробно и глубоко работала над поиском ответа на регулярно звучащий в отечественной и зарубежной социологии вопрос об общественно-политической активности и ответственности социологов. Разрешение указанного противоречия представляется особенно важным с учётом потенциального роста значимости социологов как социально активной, ориентирующей экспертной группы в условиях социально-политической нестабильности. Цель работы – определить предположительные препятствия расширению актуального социологического интереса к наследию Франкфуртской школы, а также указать наиболее значимые, с точки зрения актуализации, качества и элементы этого наследия. The critical sociology of the Frankfurt School is artificially limited on vocabularies and textbooks by the Ukrainian sociological discourse. The active use of its ideas is not a tradition in modern Ukrainian sociology. But critical sociology worked detailed and deep to find answers to the important sociological question of socio-political activity and responsibility of sociologists. This contradiction needs to be resolved. Especially in view of growing social and political instability and the rise of right-wing forces in Ukraine. Purpose of paper is to find out what hinders the expansion of the current sociological interest in the heritage of the Frankfurt School, as well as to specify the most relevant elements of the quality and heritage. There are listed not all elements of the critical sociology of Frankfurt School, which make this theory relevant to modern Ukrainian sociology. But it is important, that we have listed the elements prevent the actualization of ideas of critical sociology in Ukrainian sociological academic discourse. The situation is not paradoxical: critical attitude is often a luxury quality for science, especially in the difficult situation of social and political instability in Ukraine nowadays. There are a lot of benefits from updating Ukrainian sociology by the ideas of the Frankfurt School.
Critical Sociology of the Frankfurt School: Between Science and Ideology
Keywords: критическая социология; Франкфуртская школа; идеологичность; академический социологический дискурс; Critical Sociology; Frankfurt School; Ideology; Academic Sociological Discourse